Edukasi dan Penilaian Kesehatan Perumahan di Wilayah Pesisir Kecamatan Ampenan Kota Mataram - Iwan Desimal; Ismail Marzuki; Arif Sofyandi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
A healthy settlement is a place to live permanently, functioning as a place to live, rest, recreation and as a place of refuge from environmental influences that meet physiological and psychological requirements, free from illness and accident. Ampenan District is located in the western region of Lombok Island and is one of the famous coastal areas for tourist destinations. One of them is Ampenan Beach. It is a common concern that in this area there are rows of houses whose health needs to be considered so that they do not become a source of risk of disease transmission such as tuberculosis, pneumonia and other environment-based diseases related to the home environment. Education is needed to increase the knowledge of residents to avoid environmental-based diseases, especially the residential environment. The method used in community service is to provide understanding and knowledge of liveable healthy homes in the residents of Karang Bunyuk, Ampenan District, Mataram City. Education and assessment of healthy homes is carried out door-to-door (from house to house). Educational media in the form of brochures containing knowledge about calm and healthy homes. Healthy home assessments were carried out on 25 residents' house. Based on the results of a survey we conducted on 25 houses in the Karang Buyuk environment, Ampenan District, it was found that there were 2 houses that met the healthy home standards and 23 houses that did not meet the healthy home standards